Genetic improvement in resistance to Striga in tropical maize hybrids - Menkir, A.; Meseka, S. (Wiley, 2019)
Striga hermonthica (Del.) Benth parasitizes maize (Zea mays L.) in sub-Saharan Africa, causing yield losses of up to 100% under severe infestation. Hybrid maize breeding for polygenic resistance to Striga has been undertaken at the International Institute of Tropical Agriculture (IITA) since the 1980s. This study was conducted to estimate genetic gain in grain yield and associated traits in a set of 32 maize hybrids developed over three breeding periods under artificial Striga-infested and noninfested conditions for 4 yr. The results of regression analyses showed a linear annual yield gain of 3.2% with a mean increase of 93.7 kg ha−1 yr−1 under Striga infestation, much of which was primarily associated with significant reductions of 2.6% yr−1 in Striga damage symptoms and 5.5% yr−1 in the number of emerged parasites at 10 wk after planting. Other traits associated with grain yield including plant height and number of ears per plant increased, whereas silking days, ear aspect, and anthesis–silking interval decreased over time. On average, hybrids developed after the 1990s yielded 64% more and displayed 61% less parasite emergence and 30% less parasite damage at 10 wk after planting compared with hybrids developed before the 1990s. These improvements were achieved with increases in grain yield, early silking, reduced anthesis–silking interval, and resistance to ear rot under noninfested conditions. The trends in breeding progress achieved during this time period appear to be in the right direction, highlighting the potential that exists to further reduce yield losses to S. hermonthica in hybrids.